The Influence of France on the Economic Development of the Second Polish Republic in the First Years after Regaining Independence: An Outline of the Problem - Ambrochowicz-Gajownik, Anna (Faces of War, 2025)
This text aims to highlight the issue of building Polish-French economic relations in the first years after Poland regained independence. For the Polish state at that time, a key concern was securing French support in the political, military, and economic spheres. For victorious France, however, economic matters were at least as important as political issues, and perhaps even more significant in relations with Poland. This was evident when the Republic of Poland was contesting the eastern territories or asserting its rights in Silesia. Primarily, the French side — particularly entrepreneurs with influence over politicians — was interested in investing capital, which consequently translated into pressure during negotiations with the Polish government. Poland did not acquiesce to all demands; nevertheless, it was keen to finalise economic agreements and conclude a trade treaty, the signing of which was made conditional upon the implementation of the political accord and the secret military convention of 1921. Another important aspect of economic relations was the exchange of goods and the principles governing such exchanges. Commercial transactions were based chiefly on preferential customs concessions granted to the French side. The negotiations culminated in the signing of the trade treaty in 1922, which stipulated numerous benefits and privileges for the French state.